MECHANICAL PROPERTIES OF SUGAR PALM (ARENGA PINNATA) ROPES AND NETS FOR AGRICULTURAL PURPOSES - Mohamad Jahja; Kasim Dihuma; Dewa Gede Eka Setiawan; Tsutomu Yamaguchi; Andi Patiewere Metaragakusuma; Masayuki Sakakibara (Jambura Physics Journal, 2023)
Sample of Arenga Pinnata (AP) fibres, ropes and nets were prepared from AP ropes using traditional tools. The ropes and nets were used as agricultural material such as vertical farming of vines (passion fruit, grape, bitter gourd, and melon) in Gorontalo and Japan. The combination of nets and vines acts as green curtain (GC) which. Could mitigate the thermal energy in outdoor as well as indoor buildings. and tested with the deformation rate of up to the point of rupture. To avoid the failure of ropes and nets on supporting the weight of the vines, the Universal Testing Machine Model WDW-50 were used to determine the ultimate tensile forces. While the physical size of the AP fibres, ropes and nets also being measured to confirm the uniformity of the individual ropes and nets